SISTEM PAKAR DIAGNOSA PENYAKIT AMBEIEN BERBASIS WEB MENGGUNAKAN METODE CERTAINTY FACTOR - Husnul Khotimah Arif; Lilis Nur Hayati; Sugiarti (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Lack of early treatment leads many patients to seek medical attention only when they have Grade IV Internal Hemorrhoids. Without proper treatment, this condition can lead to serious complications such as severe pain and anemia due to repeated bleeding. Hemorrhoids are a medical condition characterized by swelling of the veins in the anus and lower rectum, which can cause pain, itching, and bleeding during bowel movements. Hemorrhoids include 18 symptoms and are divided into six types: grades I-IV internal hemorrhoids, external hemorrhoids, and thrombosed hemorrhoids. The purpose of this research is to develop an expert system application for diagnosing hemorrhoids to help the public determine the severity of their condition. This system is built using a knowledge base obtained from doctors who have treated hemorrhoids. The Certainty Factor method helps explain the level of confidence in a symptom based on expert knowledge, so users can obtain initial information before seeking further examination by a medical professional. From the trial of 22 samples with a comparison of the system test results with experts, there were 4 that did not match, so the system obtained a percentage of 81,82% system accuracy in diagnosing hemorrhoids, so this application makes it easier for users to diagnose the type of hemorrhoids.